PENGARUH MUSIK INSTRUMENTAL TERHADAP TINGKAT KECEMASAN PADA PASIEN PRE OPERASI DI RUANG RAWAT INAP SANTO LUKAS RUMAH SAKIT UMUM SANTO VINCENTIUS SINGKAWANG - Anna Lusia; Ira Ocktavia; Juliyanti (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2023)
Preoperative actions can have a psychological impact on patients such as fear and anxiety. To overcome anxiety can be done pharmacologically and non- pharmacologically. One of the non-pharmacological therapies to reduce anxiety is instrumental music therapy. The purpose of this study was to determine the effect of instrumental music on anxiety in preoperative patients in the Lukas Inpatient Room, Santo Vincentius Hospital Singkawang. The method used is a quasi-experimental design with Pre And Post Test Without Control. Sampling was carried out using the Probability Sampling technique with the Simple random sampling technique with a total sample of 31 people. The method of data collection was using the APAIS questionnaire sheet and MP3 instrumental music. Data analysis used was univariate and bivariate analysis using the Saphiro-Wilk normality test, probability value (sig) <0.05 and non-parametric Wilcoxon test obtained p-value 0.000 <0.05. This study shows that most of the patients before being given instrumental music therapy experienced high anxiety by 51.6%, the level of anxiety after being given instrumental music decreased to moderate anxiety by 38.7%. There is an effect between before being given instrumental music therapy and after being given instrumental music therapy to preoperative patients in the St. The results of the study can be proposed as a suggestion in the management of anxiety at the General Hospital of Santo Vincentius Singkawang by using instrumental music in preoperative patients